Flexural and impact properties of kenaf bast and core fibre reinforced unsaturated polyester composites - Ishak, Mohamad Ridzwan; Wirawan, Riza; Salit, Mohd Sapuan; Leman, Zulkiflle; Abdul Manaf, Mohd Edeerozey; Othman, Intan Sharhida (2009)
The flexural and impact properties of kenaf bast and core fibre reinforced unsaturated polyester composites with varying fibre weight fraction i.e. 5%, 10%, 20%, 30% and 40% have been carried out in this study. Flexural and impact tests were carried out in accordance to the ASTM D790 and D256 respectively. The results showed that the optimal value to obtain the highest flexural strength for both bast and core fibre composites were 10% while for impact strength of bast and core fibre composites were 10% and 5% respectively. Then, these properties had decreased beyond these weight fractions. This was due to further increase of fibre loading attributed to insufficient resin to wetting the fibre. It also can be noted that in general, composites reinforced with kenaf bast fibre are found to have consistently higher impact strength than kenaf core fibre.